2018
DOI: 10.1523/jneurosci.0699-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Preconditioning Requires the Mitophagic Activity of C-terminus of HSC70-Interacting Protein

Abstract: C-terminus of HSC70-interacting protein (CHIP, ) is a ubiquitously expressed cytosolic E3-ubiquitin ligase. CHIP-deficient mice exhibit cardiovascular stress and motor dysfunction prior to premature death. This phenotype is more consistent with animal models in which master regulators of autophagy are affected rather than with the mild phenotype of classic E3-ubiquitin ligase mutants. The cellular and biochemical events that contribute to neurodegeneration and premature aging in CHIP KO models remain poorly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 90 publications
2
27
0
Order By: Relevance
“…However, several genes involved in the initiation of autophagosome formation including Becn1 , Atg12 , Atg4b , and Map1lc3b [ 51 ] were decreased in CHIP −/− mice when treated with fenofibrate ( Figure 6 d). These data are consistent with the role of CHIP in regulating autophagy-related pathways [ 12 , 46 , 47 , 48 , 49 , 50 ] and the disruption of regulation is more pronounced in conditions that may activate autophagy/mitophagy such as therapies that include fibrates.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, several genes involved in the initiation of autophagosome formation including Becn1 , Atg12 , Atg4b , and Map1lc3b [ 51 ] were decreased in CHIP −/− mice when treated with fenofibrate ( Figure 6 d). These data are consistent with the role of CHIP in regulating autophagy-related pathways [ 12 , 46 , 47 , 48 , 49 , 50 ] and the disruption of regulation is more pronounced in conditions that may activate autophagy/mitophagy such as therapies that include fibrates.…”
Section: Resultssupporting
confidence: 87%
“…These pathways in the heart are activated by several cardio-protective compounds [ 42 ] including fenofibrate [ 43 , 44 , 45 ]. Moreover, CHIP is known to play an important role in autophagy [ 12 , 46 , 47 , 48 , 49 , 50 ]. To explore the mechanism behind the phenotype observed in CHIP −/− mice, we used qPCR analysis to determine if fenofibrate had differential effects on metabolic or autophagy/mitophagy gene expression in hearts isolated from CHIP −/− versus wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
“…BAG5, a member of a larger family of proteins, directly interacts with HSP70 and inhibits HSP70-mediated refolding of misfolded proteins 39 . Both STUB1and BAG5 are related to pathways of cellular response to stress and protein kinase and chaperone binding to target proteins for degradation [38][39][40][41] . In addition, it has been reported that diseases associated with BOLL include azoospermia and male infertility 42-44 . We observed significantly increased abundance of STUB1 in Chr18 ∆/∆ testes compared to controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, SCAR16 patients with cognitive dysfunction and Ubox mutations may benefit from the use of molecular chaperones to prevent the oligmerization of these mutant CHIP proteins. CHIP impacts several cellular pathways, and identifying the CHIP-dependent pathways that may contribute to the specific pathologies in SCAR16, such as necroptosis (28), IGF1 (29), mitophagy (30), autophagy (31,32), or water balance (33), may also uncover therapeutically relevant targets. Additionally, gene therapy approaches might be applicable to SCAR16.…”
Section: Discussionmentioning
confidence: 99%